El fracturamiento hidráulico en yacimientos no convencionales a partir de fuentes hídricas superficiales y acuíferos subterráneos, y su impacto en el recurso hídrico y en la salud humana (2023)
The fundamental objective of this research lies in the identification of the sources of contamination that affect both surface and groundwater due to the hydraulic fracturing process, and in the thorough evaluation of the adverse effects that this contamination exerts on human health. In a first stage, an clarifying context is provided about the hydraulic fracturing procedure and the origin of the aquifer sources, both those visible on the surface and those hidden underground. Subsequently, the various types of contaminants that affect these water sources are outlined. This study carries out an exhaustive analysis of the main causes and repercussions linked to the contamination of surface and groundwater as a direct result of the hydraulic fracturing process. Specifically, the essential chemicals used in this process are carefully examined and their impact on both the water supply and human health is evaluated. The main focus is on achieving a deep understanding of the effects of hydraulic fracturing on water sources and human health. Ultimately, the final purpose of this research is to suggest preventive measures and mitigation strategies that efficiently counteract the detrimental effects that this technique could generate on the natural environment and surrounding communities.